The Malaysian millennia’s intention to use mobile payment systems– extending the mobile technology acceptance model - Chong, Pui See (2023)
Mobile commerce is becoming an important tool for shopping among residents in developed and developing countries. Advances in mobile payment (mpayment) systems benefit sellers and users in terms of instant payment service using mobile devices. However, the adoption of m-payment is not flourishing in Malaysia. Malaysians are hesitant to use the m-payment system proactively, even though they may have realized the benefits of e-commerce. In order to address this issue, this project examines the key behavioral variables - the usefulness of m-payment systems; ease-of-use of m-payment systems; perceived trust; and perceived mobility – in influencing customers' intentional behavior. Millennial is targeted in this project because the groups represent a large and lucrative potential market for m-payment merchants due to their technological knowledge, busy schedules, and higher purchasing power. The current conceptual model is based on the MTAM framework, enriched by adding two more variables: perceived trust and perceived mobility. The questionnaire was distributed by snowball sampling method, and variable items were measured by 5 points Likert scale. 384 answered questionnaires were collected. The results show that the usefulness and ease-of-use of m-payment system and perceived trust are positively significant with respondents’ intentional behavior and appropriate implications are suggested to academics and managerial decision-makers. Plausible explanations on the non-significant effect created by perceived mobility, research limitations, and suggestion for future research are presented.